Extraterritorial Jurisdiction as a Practical Solution to Tackle Transnational Animal Welfare Issues - Maulidya Candra Dwi Putri; Habib Adjie (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The globalization of industrial animal agriculture including exportation of live animals has brought farm animals as the victims of global trade. Farm animals are still treated as commodities in most jurisdictions. They are the animals that suffer the most as they are mostly bred, kept and raised in intensive confinement just to be used or killed by humans. The farm animals are mostly treated inhumanely with no legal protection. Although global awareness regarding animal welfare has arisen, the development of animal law in national and international regulations has not changed much, especially regulation of farm animals. This journal will suggest a solution to the issues which arise regarding the farm animals’ welfare through the WTO laws and extraterritorial jurisdiction. Extraterritorial jurisdiction is introduced in this journal as it is believed to be a practical solution to fill the regulatory gaps regarding farm animals’ welfare that transported globally.